From Buenos Aires to Santa Fe – Darwin’s observations and modern knowledge - Iriondo, Martin Horacio (2009)
During his historical travel around the world, Darwin raided deeply in the South American interior, travelling more than 600 kilometers from Buenos Aires to the north along the Paraná River. During that journey, he crossed a large plain characterized by aeolian sediments, something not familiar to a European naturalist. However, Darwin’s acute observation capacity and precise descriptions are noteworthy. After more than 170 years since Darwin’s visit, modern geological knowledge identifies several sectors in the Buenos Aires-Santa Fe region, one of them (the Tertiary at La Bajada) he described admirably and others such as the Paraná flood plain were brilliantly abstracted in only two sentences. In short, Darwin traversed a first sector (Buenos Aires-Rosario) characterized by aeolian and paludal Early Pleistocene sediments. From Rosario to Santa Fe the plain is formed by Late Pleistocene aeolian and fluvial units. At La Bajada (today Paraná city) lies exposed the marine Miocene and in SW Entre Ríos is a reconstructed loess-paleosol sequence generated at the Early/Middle Pleistocene transition. The Paraná flood plain and the littoral complex at the mouth (practically not observed by Darwin) underwent rather complex Holocene episodes.